An Improved Optimization Model of Internet Charging Scheme in Multi Service Networks - Kamaruzzaman Seman; Fitri Maya Puspita; Bachok M. Taib; Zurina Shafii (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
This article will analyze new improved charging scheme with base price, quality premium and QoS networks involved. Sain and Herpers [5] already attempted to obtain revenue maximization by creating charging scheme of internet. The plan is attempted to solve multi service networks scheme as an optimization model to obtain revenue maximization using our improved model based on Byun and Chatterjee [2] and Sain and Herpers [5]. The results show that improved model can be solved optimally using optimization tool LINGO to achieve better revenue maximization. Better results are obtained in all cases rather than in [5]. The advantage of our new model is that ISP also can set up their base price and quality premium based on ISP preferences. For some cases for getting revenue maximization, we do not offer one service and just utilize some of the services.